A case study on particulate emissions from a gasoline plug-in hybrid electric vehicle during engine warm-up, taking into account start–stop operation. (November 2020) - Lenz, Martin; Cremer, Moritz; Guse, Daniel; Röhrich, Henning; Pischinger, Stefan
Concerning the discussions about emissions caused by individual mobility, it is foreseeable that future vehicle concepts will increasingly be based on hybrid powertrains. These systems lead to more complex operating scenarios, which have a significant influence on the resulting emissions of the engine. This work shows a case study and the results in the operation and emission behavior of a plug-in hybrid electric vehicle with a direct injection gasoline engine when operated in an internationally recognized driving cycle. The vehicle's exhaust aftertreatment system consists of a three-way catalytic converter; a particulate filter is not installed. The emissions are analyzed with a focus on particulate number emissions (from soot), especially during the warm-up phase and the frequent start–stop events (in total, there are 12 internal combustion engine operating phases), which are typical for hybrid vehicles. The results show that approximately 50% of the emitted particulates have a smaller size, 23 nm (a very high number of particulates with a mean size of 10 to 15 nm are present), which are currently not regulated, but are expected to have a high risk of adverse health effects.